(untitled) (Analysis of International Sciences, 2024)
all students-young people, artists should be engaged in their favorite sports, physical exercises, in the process of health improvement. Anatomical and physiological characteristics of the body of children and adolescents; The central nervous system and, first of all, its upper part, the cerebral cortex, play a leading role in the development of body functions.